VTC2000-Spring. 2000 IEEE 51st Vehicular Technology Conference Proceedings (Cat. No.00CH37026)
DOI: 10.1109/vetecs.2000.851429
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of streaming data over an EGPRS wireless network

Abstract: Abstract| W e investigate the feasibility o f transmitting MPEG-2 AAC Advanced Audio Coder music over packetswitched bearers of an Enhanced General Packet Radio Services cellular network. Streaming data applications like AAC music di er from conversational voice in that they permit a larger transmission delay and delay jitter than the former. In addition, AAC m usic can tolerate a higher frame error rate than voice by using error concealment techniques at the receiver. This creates the opportunity t o transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In [7], we explored a mechanism to estimate the sustainable channel rate based on measured interference, prior to initiating the video session. Video quality was significantly improved by choosing a suitable transmission rate for a user based on observed channel characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In [7], we explored a mechanism to estimate the sustainable channel rate based on measured interference, prior to initiating the video session. Video quality was significantly improved by choosing a suitable transmission rate for a user based on observed channel characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In [7] we examined system issues associated with transporting one-layer video over EGPRS. We found that linklayer adaptation, error control, and retransmissions are important factors in providing good video quality to most users.…”
Section: Egprs Network and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such solutions exploit the scalability offered by recently standardized compression formats. Several of these rate-control solutions have been targeted towards erroneous channels (e.g., [19], [7], [20], [14], [3], [2]; see also [26], [27], [28] and the references therein). The authors in [13] formulated an optimization problem that considers as design parameters the end-to-end delay, the policing constraints, and the encoder and decoder buffer sizes.…”
Section: Introductionmentioning
confidence: 99%